Laser microdissection expression profiling of marginal edges of colorectal tumours reveals evidence of increased lactate metabolism in the aggressive phenotype. Issue 3 (31st October 2008) - Thorn, C C; Freeman, T C; Scott, N; Guillou, P J; Jayne, D G
Abstract : Background: The morphology of the invasive margin in colorectal cancer can be described as either pushing or infiltrative. These phenotypes carry prognostic significance, particularly in node negative disease, and provide an excellent model for the study of invasive behaviour in vivo. Methods: The marginal edges of 16 stage-matched tumours exhibiting these contrasting growth patterns were microdissected. The extracted mRNA was amplified and hybridised to a 9546 feature oligonucleotide array. Selected differentials were validated using real-time polymerase chain reaction and the protein product was interrogated by using immunohistochemistry. Results: After stringent quality control and filtering of data generated, 39 genes were identified as being significantly differentially expressed between the two types of marginal edge. Several genes involved in cellular metabolism were identified as differentials including lactate dehydrogenase B (LDHB) and modulators of glucose transport. Conclusions: The LDH expression profile differs between the invasive phenotypes. A hypothesis is proposed in which altered metabolism is a cause of contrasting invasive behaviour independent of the hypoxia-inducible factor mediated hypoxic response, consistent with the Warburg phenomenon.